Parasitism of Sclerotium rolfsii by Trichoderma - E. SCHLOSSER2, SUSEELENDRA DESAI1 and (Indian Phytopathology, 2002)
Forty-four isolates of Trichoderma belonging to 8 species groups were tested for their ability to infect, macerate and kill the sclerotia of S. rolfsii [Corticium rolfsii]. While 14 isolates infected and killed sclerotia of C. rolfsii, 17 isolates were not effective, and the remaining isolates showed an intermediate effect. Eight isolates of T. harzianum and only 3 isolates each of T. hamatum and T. koningii could kill all the sclerotia inoculated. The biocontrol agent could penetrate the sclerotial wall, establish and sporulate inside the sclerotium.